Vitamin D Deficiency During Pregnancy and Autism Spectrum Disorders Development - Principi, Nicola; Esposito, Susanna (Frontiers in Psychiatry, 2020)
Autism spectrum disorder is a neurodevelopmental disorder characterized by reduced social interactions, impaired communications and stereotypic and repetitive behaviour with different degrees of severity. The aetiology of autism spectrum disorder is unknown, although the interaction of genetic and environmental factors is believed to play a fundamental role in the process. The main aim of this narrative review is to discuss the current knowledge about the interrelationships between vitamin D deficiency during pregnancy and autism spectrum disorder development. Literature analysis showed that vitamin D supplementation during pregnancy plays a role in conditioning the development and function of the nervous system. Studies carried out in vitro and in experimental animals have shown that vitamin D deficiency can be associated with structural and functional abnormalities of the nervous system that can be observed in autism spectrum disorder patients. Moreover, it has been reported that vitamin D deficiency during pregnancy could be a risk factor for autism spectrum disorder development in the offspring, that children with autism spectrum disorder have significantly lower serum levels of vitamin D than normal children and that supplementation of vitamin D in autism spectrum disorder children is associated with a reduction in psychiatric manifestations. However, the data currently available do not adequately support the hypothesis that vitamin D may be a factor which contribute to the aetiology of autism spectrum disorder. The effects of vitamin D supplementation during pregnancy should be better studied to establish whether and when foetal vulnerability is highest and if vitamin D supplementation is able to reduce the risk of structural and functional alterations of the nervous system and autism spectrum disorder development. The role of vitamin D after birth must be better defined to evaluate if vitamin D administration is potentially effective in reducing autism spectrum disorder manifestations.